Anti-IL-5 and anti-IL-5 receptor therapy significantly improves quality of life and FEV1 values in patients with severe asthma - Anaiza Odalis Villalobos Alfaro; Haydee Carolina Gutiérrez Vargas; Juan Manuel Díaz; Jonathan Alvarez Pinto; Diana Cristina García Cambero; Eduardo Hernandez Cuellar; Julio Augusto Palma Zapata; Alondra Esthefanía Llamas Domínguez; Juliana Palma Zapata; Silvia Denise Ponce-Campos (Allergy, Asthma & Clinical Immunology)
Abstract In recent years, the use of monoclonal antibodies directed against interleukin-5 (anti-IL-5) and its receptor alpha (anti-IL-5R) has proven to be an effective therapeutic option for patients with severe asthma by reducing the number of eosinophils, which may promote disease remission. This study aimed to evaluate clinical improvement and remission in patients with severe asthma treated with anti-IL-5 and anti-IL-5R antibodies over a period of 12 months. A cohort study was conducted with 49 patients diagnosed with severe eosinophilic asthma and who did not respond to conventional treatment. During follow-up, medical control was performed every 3 months using spirometry, eosinophil counts, quality of life scales, and disease control. The results revealed an improvement in FEV1 after 3 months of treatment, with statistical significance at 12 months in patients treated with anti-IL-5 and at 9 months in those treated with anti-IL-5R. In addition, better perceptions of asthma control and quality of life were observed, with significant differences at 6 and 12 months. Correlations between spirometry and ACT, ACQ, and AQLQ reflect a progressive recovery of well-being and function. Finally, the remission rate was 41.1% with anti-IL-5 treatment and 47.3% with anti-IL-5R treatment after one year of follow-up. These findings support the efficacy of anti-IL-5 and anti-IL-5R treatment in improving severe asthma control and patients’ quality of life, suggesting their key role in disease remission.